Allocation under Uncertainty when the Demand has Continuous D.F. - Elmaghraby, Salah E. (Management Science, 1960)
The problem of allocation under uncertain demand, when the latter has a continuous distribution function, is treated. A necessary and sufficient condition for optimality is given, and a numerical example is solved. This solution is compared with the L.P. solutions obtained under the assumptions of constant demand and demand with discrete d.f. It is seen that considerable savings can be realized by considering d.f.'s as continuous if they so occur in nature.